Thoracic anaesthetic research: 90 years of sustained progress. (January 2023) - Shelley, Ben; Licker, Marc; Slinger, Peter
Summary: Over the 90 years since the first description of one-lung ventilation, the practice of thoracic surgery and anaesthesia continues to develop. Minimally invasive surgical techniques are increasingly being used to minimise the surgical insult and facilitate improved outcomes. Challenging these outcomes, however, are parallel changes in patient characteristics with more older and sicker patients undergoing surgery. Thoracic anaesthesia as a speciality continues to respond to these challenges with evolution of practice and strong academic performance.